Faktor Pemungkin dan Penguat Perilaku Ibu Membawa Anaknya ke Pos Pelayanan Terpadu (Posyandu) - Mergy Gayatri; Dian Kusumaningtyas; Lidya Drajat Pramesti; Siti Karomah (Journal of Issues in Midwifery, 2022)
The integrated service post program (in Indonesian: posyandu) aims to reduce infant mortality, and maternal mortality rates. However, the coverage of posyandu visits in Singosari sub-district was low (<50%) in 2021; hence this study aims to identify enabling and reinforcing factors of the behavior of posyandu visits. This research was conducted in Banjarum Village on 61 mothers who have toddlers. The survey instrument was used to identify factors related to the behaviour of visiting the posyandu under five. The results of the enabling factors showed that 88.52% of mothers had a health card, 93.44% of mothers said their children did not receive immunisation at the posyandu for during the last three months, and 100% of mothers added that the posyandu had a supplementary food provision program. The results of the enabling factors show that 100% of mothers have the support of family and community leaders to bring their toddlers to visit the posyandu, and say they need a posyandu in their residence. There was no significant relationship between enabling factors and the behaviour of mothers who brought their children to the posyandu under five (p ³ 0.05). This study includes a small number of respondents and was conducted during the COVID-19 pandemic, therefore further research can be carried out on a larger sample size and during periods outside the pandemic.